TRANSFORMATION PROCESSES IN ECONOMIC ACTIVITIES KIEV REGION IN THE CONTEXT OF THEIR INFLUENCE ON EMPLOYMENT - Воловик, Людмила (Human Geography Journal, 2015)
The effect of transformation processes in economic activities of the Kiev region on employment. Characterized the role and importance of natural resource potential in the specialization of economic activities, identify new forms of production organization, has clarified the employment and labor market formation. A comparative analysis of employment peripheral and suburban areas of the capital. Are characterized socio-economic relationships with the capital Kyiv region, including economic feasibility of placing branches of metropolitan industrial enterprises and organizations in Kyiv suburbs and outlying areas.